2007
DOI: 10.3113/fai.2007.1160
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic Toe Ulcers Treated with Toe Flexor Tenotomies

Abstract: No long-term results of treating toe ulcers with toe flexor tenotomy by other authors have been found. Toe flexor tenotomies appear to be effective and safe treatment for neuropathic toe ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(85 citation statements)
references
References 19 publications
4
80
1
Order By: Relevance
“…5,6 The few published reports on tenotomies have up to 100% ulcer healing rate, 14,18 as did Laborde in a retrospective study of 18 patients with 28 ulcers. 8 The latter study reported 3 hallux ulcers recurring within 36 months. In a retrospective study of 48 patients with 58 flexor tenotomies, Kearney et al reported a 98% healing rate, with 5% suffering a postoperative infection and 12% experiencing a recurrence in 28 months of follow-up.…”
Section: Discussionmentioning
confidence: 89%
“…5,6 The few published reports on tenotomies have up to 100% ulcer healing rate, 14,18 as did Laborde in a retrospective study of 18 patients with 28 ulcers. 8 The latter study reported 3 hallux ulcers recurring within 36 months. In a retrospective study of 48 patients with 58 flexor tenotomies, Kearney et al reported a 98% healing rate, with 5% suffering a postoperative infection and 12% experiencing a recurrence in 28 months of follow-up.…”
Section: Discussionmentioning
confidence: 89%
“…Adjunctive treatment of diabetic ulcerations by lengthening, rerouting, or transecting tendons in the lower extremity has been previously described (9)(10)(11)(12)(13)(14). Specifically, lengthening of the tibialis anterior tendon has been successfully used for surgical treatment of clubfoot (15).…”
Section: Discussionmentioning
confidence: 98%
“…If regular debridement and off-loading (toe crest pads, shock attenuating insole materials, casting, etc) do not resolve the ulcer or the ulcer recurs, and the deformity is reducible, then surgical release of the long flexor should be considered. 54,63 Laborde 54 retrospectively evaluated 28 toe ulcers that were treated with a percutaneous flexor tenotomy ( Figure 6), with at least 20 months of follow-up. It was found that 17 (61%) of the toes with ulceration were the great toe.…”
Section: Ulcers On the Tip Of The Toementioning
confidence: 99%